Design and Implementation of a Switched Capacitor-Based Single-Phase 15-Level Inverter for Renewable Energy Applications - K, Manikandan; Raj L, Hubert Tony; P, Venkatesh; Kumar A, Mathan; S, Gokul; A, Anand (Journal of Neonatal Surgery, 2025)
In grid-connected solar photovoltaic (PV) systems, galvanic isolation is essential. Despite the growing use of multilevel inverters (MLIs) in grid-tied applications, the literature currently available only briefly examines isolated MLI topologies. In this study, a new 15-level isolated MLI design that requires only thirteen power switches to operate is presented. An upper and a lower unit are the two primary units that make up the suggested architecture. A traditional H-bridge inverter is used for the upper unit, while a switched-capacitor-based five-level design is used for the lower unit. The most notable aspect of this design is its capacity to generate a 15-level Alternating output voltage with a enhancing voltage of 7 and the fewest number of switches needed. The suggested arrangement puts its switches under less voltage stress than current multilayer inverter topologies, improving reliability. MATLAB simulation software is used to evaluate the inverters performance under many operating scenarios. The results demonstrate that even at lower modulation indices, the inverter produces high-quality output and maintains steady capacitor voltage levels. A low-power prototype is used for experimental validation, which verifies the inverter's functionality. Practical testing at a 710Watts output shows an efficiency of 96.5%, whereas the simulation-based efficiency is measured at 97.2%.